2007
DOI: 10.11606/issn.1678-4456.bjvras.2007.26606
|View full text |Cite
|
Sign up to set email alerts
|

Implante de tendão autógeno do músculo flexor superficial dos dedos no reparo de desvio do pênis de bovinos

Abstract: Dezoito novilhos mestiços, com idade entre 16 e 20 meses, foram submetidos à remoção do ligamento apical do pênis para provocar o seu desvio. Decorridos 60 dias os animais foram colocados em presença de fêmeas em estro, sendo verificado formação de desvios ventral e lateral direito do pênis, com incapacidade de cópula. Os bovinos foram submetidos ao transplante autólogo de um segmento do tendão da porção superficial do músculo flexor superficial dos dedos, sobre a túnica albugínea, substituindo o ligamento api… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 4 publications
1
4
0
1
Order By: Relevance
“…The successful experimentally induced penile deviation through removal of a fragment of the penile apical ligament of the bulls highlights the importance of this structure in the pathogenesis of this disease (Eurides et al 2007). A higher incidence of right lateral (62%) versus ventral (38%) deviation, as observed in this study, was also previously reported for the experimental induction of penile deviation by means of a section of the apical ligament (Eurides et al 1994).…”
Section: A D E B C Fsupporting
confidence: 85%
See 4 more Smart Citations
“…The successful experimentally induced penile deviation through removal of a fragment of the penile apical ligament of the bulls highlights the importance of this structure in the pathogenesis of this disease (Eurides et al 2007). A higher incidence of right lateral (62%) versus ventral (38%) deviation, as observed in this study, was also previously reported for the experimental induction of penile deviation by means of a section of the apical ligament (Eurides et al 1994).…”
Section: A D E B C Fsupporting
confidence: 85%
“…This event was observed whit the use of autologous tendon of the superficial flexor muscle and autologous auricular cartilage in bulls to repairing penile deviation (Eurides et al 2007, Eurides et al 2009.…”
Section: A D E B C Fmentioning
confidence: 94%
See 3 more Smart Citations